Improving perioperative management of surgical sets for trauma surgeries: the 4S approach - Julio Ribes-Iborra; Borja Segarra; Victor Cortés-Tronch; Javier Quintana; Thibaut Galvain; Christian Muehlendyck; Elena Escalona; Suzanne Battaglia; Jorge Navarrete-Dualde (BMC, 2022)
Abstract Background The perioperative management of the surgical instruments and implants that comprise sets for trauma surgeries has been identified as a complex and resource-intensive activity due to non-standardized inventories, redundant surgical instruments and unnecessary sterilization cycles. The 4S Intelligent Trauma Care program aims to improve perioperative management and thereby reduce environmental impact by utilizing standardized inventories, a sterile implant portfolio, a barcode that enables a digital safety certification, and a digitized restocking service. Objective The objective of this study was to investigate the impact of the introduction of the 4S program for the management of surgical sets in open reduction internal fixation (ORIF) trauma surgeries. Methods This was a single-center, quality improvement study of ORIF trauma surgeries, comparing the current practice (30 procedures) to the procedure following the introduction of the 4S program (30 procedures). The primary outcome was the proportion of procedures requiring only one sterilization cycle. Secondary outcomes were the number of sterilization cycles per procedure, set processing time across departments, total set processing costs, number of missing or damaged implants, number of cleaning cycles per procedure, time taken to assemble containers for sterilization, number of containers entering the autoclave per procedure, environmental impact, number of baskets entering the cleaning machine per procedure, and staff satisfaction. Results Introduction of the 4S program resulted in a reduction in the mean number of sterilization cycles required from 2.1 to 1.0 (p < 0.001). In the current practice, only 30.0% of procedure sets were sterilized within one cycle, compared to 100.0% following introduction of the 4S program (p < 0.001). A reduction in the mean set processing time of 24.1% in the OR and 35.3% in the sterilization department was observed. Mean set processing costs for the current practice were €81.23, compared to €50.30 following introduction of the 4S program. Furthermore, following the introduction of the 4S program, procedures were associated with significant reductions in water and electricity usage, and increased staff satisfaction. Conclusions This quality improvement study demonstrates the substantial time and cost savings, positive environmental impact and staff satisfaction that could be achieved by streamlining surgical set management through the 4S program. To our knowledge, this is the first study of this type and our findings may be instructive to other hospitals and surgical specialties.